Moderate Photoinhibition of Photosystem II Protects Photosystem I from Photodamage at Chilling Stress in Tobacco Leaves - Huang, Wei; Yang, Ying-Jie; Hu, Hong; Zhang, Shi-Bao (Frontiers in Plant Science, 2016)
It has been indicated that photosystem I (PSI) is susceptible to chilling-light stress in tobacco leaves, but the effect of growth light intensity on chilling-induced PSI photoinhibition in tobacco is unclear. We examined the effects of chilling temperature (4°C) associated with moderate light intensity (300 μmol photons m−2 s−1) on the activities of PSI and photosystem II (PSII) in leaves from sun- and shade-grown plants of tobacco (Nicotiana tabacum cv. k326). The sun leaves had a higher activity of alternative electron flow than the shade leaves. After 4 h chilling treatment, the sun leaves showed significantly a higher PSI photoinhibition than the shade leaves. At chilling temperature the sun leaves showed a greater electron flow from PSII to PSI, accompanying with a lower P700 oxidation ratio. When leaves were pre-treated with lincomycin, PSII activity decreased by 42% (sun leaves) and 47% (shade leaves) after 2 h exposure to the chilling-light stress, but PSI activity remained stable during the chilling-light treatment, because the electron flow from PSII to PSI was remarkably depressed. These results indicated that the stronger chilling-induced PSI photoinhibition in the sun leaves was resulted from a greater electron flow from PSII to PSI. Furthermore, moderate PSII photoinhibition depressed electron flow to PSI and then protected PSI activity against further photodamage in chilled tobacco leaves.